Tubular Aggregates and Cylindrical Spirals Have Distinct Immunohistochemical Signatures. Issue 12 (December 2016) - Brady, Stefen; Healy, Estelle G.; Gang, Qiang; Parton, Matt; Quinlivan, Ros; Jacob, Saiju; Curtis, Elizabeth; Al-Sarraj, Safa; Sewry, Caroline A.; Hanna, Michael G.; Houlden, Henry; Beeson, David; et al.
Abstract : Tubular aggregates and cylindrical spirals are 2 distinct ultrastructural abnormalities observed in muscle biopsies that have similar histochemical staining characteristics on light microscopy. Both are found in a wide range of disorders. Recently, a number of genetic mutations have been reported in conditions with tubular aggregates in skeletal muscle. It is widely accepted that tubular aggregates arise from the sarcoplasmic reticulum, but the origin of cylindrical spirals has been less clearly defined. We describe the histopathological features of myopathies with tubular aggregates, including a detailed immunohistochemical analysis of congenital myasthenic syndromes with tubular aggregates due to mutations in GFPT1 and DPAGT1, and myopathies with cylindrical spirals. Our findings support the notion that cylindrical spirals, like tubular aggregates, derive primarily from the sarcoplasmic reticulum; however, immunohistochemistry indicates that different molecular components of the sarcoplasmic reticulum may be involved and can be used to distinguish between these different inclusions. The immunohistochemical differences may also help to guide genetic testing.